Frank Porter Graham : Southern Liberal, Citizen of the World - Link, William A. (Book collections on Project MUSE., 2021)
"Frank Porter Graham (1886-1972) was one of the most consequential white southerners of the twentieth century. Born in Fayetteville and raised in Charlotte, he taught history at UNC, and in 1930, he became the university's fifteenth president. Affectionately known as 'Dr. Frank,' Graham spent two decades overseeing UNC's development into a world-class public institution. But he regularly faced controversy, especially as he was increasingly drawn into national leadership on matters such as intellectual freedom and the rights of workers. As a southern liberal, Graham became a prominent New Dealer, negotiator, and briefly a U.S. senator. Graham's reputation for problem solving through compromise led him into service under several presidents as a United Nations mediator, and he was outspoken as a white southerner regarding civil rights. Brimming with fresh insights, this definitive biography reveals how a personally modest public servant took his place on the national and world stage and, along the way, helped transform North Carolina"--